2020
DOI: 10.18502/ijps.v15i3.3810
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Talk in Predicting Death Anxiety, Obsessive-Compulsive Disorder, and Coping Strategies in the Face of Coronavirus Disease (COVID-19)

Abstract: Objective: Nowadays, the outbreak of Coronavirus (COVID-19) is one of the most stressful resources that has led to the rise of different levels of psychological crisis. In addition to the countries affected by the COVID-19, such as China, European and American countries, Iran has appeared as one of the most affected countries with high infected cases and deaths. Thus, the purpose of this study was to investigate the role of self-talk in predicting death anxiety, obsessive-compulsive disorder, and coping strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
1
24
1
2
Order By: Relevance
“…Although the morbidity of COVID‐19 is not as high as that of SARS, patients commonly suffering a certain degree of death anxiety that harmed their recovery (Dar et al., 2017 ; Huang et al., 2020 ; Sadri Damirchi et al, 2020 ; Xiang et al., 2020 ). A previous study reported psychological conditions impacted the patients' appetite and food intake in other disease (Fysekidis et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the morbidity of COVID‐19 is not as high as that of SARS, patients commonly suffering a certain degree of death anxiety that harmed their recovery (Dar et al., 2017 ; Huang et al., 2020 ; Sadri Damirchi et al, 2020 ; Xiang et al., 2020 ). A previous study reported psychological conditions impacted the patients' appetite and food intake in other disease (Fysekidis et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, debates such as the end of the world, panic, death, and the number of cases in the media also remind about death ( € Ozyu¨rek & Atalay, 2020). With the quarantine applied to protect against pandemic, the situation of staying at home continuously, the decrease in social relations and the feelings of loneliness, the unexpected deaths of loved ones, the presence of many images reminding of death, frequent and repeated washing of the hands, and disturbing thoughts about the disease negatively affect mental health (Damirchi et al, 2020;€ Ozyu¨rek & Atalay, 2020). These factors cause psychological problems in individuals such as depression, fear (especially fear of death), anxiety of not getting adequate and efficient health care, sleep problems, anxiety (especially death anxiety) (Okuyan et al, 2020).…”
mentioning
confidence: 99%
“…Adaptation to the situation seems crucial, and the current study showed that Spanish athletes adjusted to the confinement situation better than Polish respondents. As studies reveal strategies such as self-talk, problem-centered coping, cognitive reconstructive and emotional calm could be helpful to regulate in those diffcult pandemic times [7,22]. Training conditions were also one of the variables which differed between the countries.…”
Section: Discussionmentioning
confidence: 99%